2015
DOI: 10.1016/j.rbmo.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mid-luteal serum progesterone concentrations govern implantation rates for cryopreserved embryo transfers conducted under hormone replacement

Abstract: This study explores the relevance of mid-luteal serum hormonal concentrations in cryopreserved embryo transfer cycles conducted under hormone replacement therapy (HRT) control and which involved single-embryo transfer (SET) of 529 vitrified blastocysts. Widely ranging mid-luteal oestradiol and progesterone concentrations ensued from the unique HRT regimen. Oestradiol had no influence on clinical pregnancy or live birth rates, but an optimal progesterone range between 70 and 99 nmol/l (P < 0.005) was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
96
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 30 publications
9
96
5
2
Order By: Relevance
“…Furthermore, vitrified-warmed blastocysts were graded twice -once prior to vitrification and again after warming with a possibly slightly poorer grade after warming and prior to transfer. While pregnancy and live birth rates are not the focus of our study, they may be affected by this difference in embryo quality (Yovich et al, 2015). Perinatal outcome, however, is most probably not affected by embryo quality as we previously reported (Oron et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, vitrified-warmed blastocysts were graded twice -once prior to vitrification and again after warming with a possibly slightly poorer grade after warming and prior to transfer. While pregnancy and live birth rates are not the focus of our study, they may be affected by this difference in embryo quality (Yovich et al, 2015). Perinatal outcome, however, is most probably not affected by embryo quality as we previously reported (Oron et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, the same range of progesterone at blastocyst transfer was seen regardless of clinical outcome ( Table 2). Earlier studies of natural conceptions in patients undergoing, and not undergoing, assisted reproduction techniques (Hull et al, 1982;Yovich et al, 1985aYovich et al, , 2015, have suggested the existence of an optimal range of luteal phase serum progesterone with an upper and a lower limit. Our data failed to support the concept of an optimal range after ovarian stimulation, as concentrations were almost identical in pregnant and non-pregnant women, and implantation rates were good, despite progesterone concentrations being eight-to nine-fold higher than in natural conception cycles (Hull et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of progesterone use after gonadotrophin releasing hormone agonist (GnRH) triggering, suggests an optimal threshold of 32-40 ng/ml of mid-luteal progesterone (Yding Andersen and Vilbour Andersen, 2014). Using oestrogen and progesterone therapy for frozen embryo transfers, Yovich et al (2015) found that a mid-luteal progesterone level between 22 and 31 ng/ml was associated with the best live birth rates. An optimal range of luteal phase steroid secretion may also exist after conventional assisted reproduction techniques with HCG triggering.…”
Section: Introductionmentioning
confidence: 99%
“…The lower pregnancy rates of the GnRHa trigger appear to be associated to a low mid-luteal phase progesterone level and probably reflect too low stimulation of the CL. Several studies have now suggested that in connection with ovarian stimulation (OS), the mid-luteal phase concentration of progesterone should exceed 100 nmol/l in order to reduce the risk of early pregnancy loss and augment reproductive outcome [12][13][14]. This concentration of progesterone is difficult to obtain through vaginal or intra-muscular administration alone and necessitates a direct stimulation of the CL with either rLH or hCG.…”
Section: Introductionmentioning
confidence: 99%